| FImpl: (*BEGIN*)Formula → Formula → Formula(*END*)
.
-let rec sem (v: nat -> nat) (F: formula) on F ≝
+let rec sem (v: nat -> nat) (F: Formula) on F ≝
match F with
[ FBot ⇒ 0
| FTop ⇒ (*BEGIN*)1(*END*)
interpretation "Formula if_then_else" 'if_then_else e t f = (if_then_else e t f).
-let rec subst (x:nat) (G: Formula) (F: formula) on F ≝
+let rec subst (x:nat) (G: Formula) (F: Formula) on F ≝
match F with
[ FBot ⇒ FBot
| FTop ⇒ (*BEGIN*)FTop(*END*)
assume F : Formula.
assume x : ℕ.
assume v : (ℕ → ℕ).
-assume H : (F1 ≡_v F2).
+suppose (F1 ≡_v F2) (H).
we proceed by induction on F to prove (subst x F1 F ≡_v subst x F2 F).
case Bot.
the thesis becomes (FBot ≡_v (subst x F2 FBot)).